Split hand/split-foot malformations: a report of four cases in a family with variable presentations - Jaiswal, Sagar Bharatlal; Soni, Sanjay Jayantilal; Patel, Chirag D.; Suthar, Ashish J. (International Journal of Research in Medical Sciences, 2017)
Split hand/split-foot malformation is a congenital anomaly with failure of development of the central digital rays of hand or foot to a variable extent. It is characterized by hypoplasia/aplasia of the phalanges, toes, metacarpals and metatarsals. The presentation may be an isolated anomaly or may be associated with syndrome and thus have variable pattern of inheritance. We report a family of 10 members; four of which are affected with autosomal recessive pattern of inheritance. We discuss here the clinical presentation, genetic inheritance, prenatal diagnosis and treatment for the malformation.